Парето-оптимальное решение многокритериальной задачи синтеза робастных регуляторов многомассовых электромеханических систем на основе многороевой стохастической мультиагентной оптимизации - Никитина, Т.Б. (Електротехніка і електромеханіка, 2017)
Усовершенствован метод многокритериального синтеза робастного управления многомассовыми электромеханическими системами на основе построения Парето-оптимальных решений и с учетом бинарных отношений предпочтения локальных критериев с помощью алгоритмов многороевой стохастической мультиагентной оптимизации, что позволяет существенно сократить время решения задачи и удовлетворить разнообразным требованиям, которые предъявляются к работе систем в различных режимах. Приведены результаты сравнений динамических характеристик электромеханических систем с синтезированными регуляторами Удосконалено метод багатокритеріального синтезу робастного керування багатомасовими електромеханічними системами на основі побудови Парето-оптимальних рішень та з урахуванням бінарних відношень локальних критеріїв за допомогою алгоритмів багатороєвої стохастичної мультиагентної оптимізації, що дозволяє істотно скоротити час вирішення задачі і задовольнити різноманітним вимогам, які пред'являються до роботи систем в різних режимах. Наведені результати порівнянь динамічних характеристик електромеханічних систем з синтезованими регуляторами. Purpose. Developed the method for solving the problem of multiobjective synthesis of robust control by multimass electromechanical systems based on the construction of the Pareto optimal solutions using multiswarm stochastic multi-agent optimization of particles swarm, which reduces the time of determining the parameters of robust controls multimass electromechanical systems and satisfy a variety of requirements that apply to the work of such systems in different modes. Methodology. Multiobjective synthesis of robust control of multimass electromechanical systems is reduced to the solution of solving the problem of multiobjective optimization. To correct the above problem solving multiobjective optimization in addition to the vector optimization criteria and constraints must also be aware of the binary preference relations of local solutions against each other. The basis for such a formal approach is to build areas of Paretooptimal solutions. This approach can significantly narrow down the range of possible solutions of the problem of optimal initial multiobjective optimization and, consequently, reduce the complexity of the person making the decision on the selection of a single version of the optimal solution. Results. The results of the synthesis of multi-criteria electromechanical servo system and a comparison of dynamic characteristics, and it is shown that the use of synthesized robust controllers reduced the error guidance working mechanism and reduced the system sensitivity to changes in the control parameters of the object compared to the existing system with standard controls. Originality. For the first time, based on the construction of the Pareto optimal solutions using a multiswarm stochastic multi-agent optimization particle algorithms improved method for solving formulated multiobjective multiextremal nonlinear programming problem with constraints, to which the problem of multiobjective synthesis of robust controls by multimass electromechanical systems that can significantly reduce the time to solve problems and meet a variety of requirements that apply to the multimass electromechanical systems in different modes. Practical value. Practical recommendations on reasonable selection of the target vector of robust control by multimass electromechanical systems. Results of synthesis of electromechanical servo system shown that the use of synthesized robust controllers reduced the error guidance of working mechanism and reduce the system sensitivity to changes of plant parameters compared to a system with standard controls